2010
DOI: 10.1021/ma902597p
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Rapid and High-Purity Monocyclic Polymers by CuAAC “Click” Reactions

Abstract: Cyclization of linear polymers by coupling end-groups together to form monocyclic polymers using the very fast Cu-catalyzed azide/alkyne cycloaddition (CuAAC) “click” reaction has been used for many polymer systems. However, the strategy based on the CuAAC methodology has not been guided by theory and relies on the very slow feed of polymer into a highly dilute reaction mixture of solvent and Cu catalyst. This leads to the production of monocyclic polymer in very low concentrations over long periods of time (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
153
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 26 publications
7
153
0
1
Order By: Relevance
“…The reason stems for the fact that the faster the reaction the faster the monocyclic will be formed in the reaction mixture, and thus higher feed rates and weight fractions of polymer can be used. 114 Lonsdale et al 12 found that they could significantly increase the weight fraction of starting polymer N 3 -PSTY-B (polystyrene, PSTY) through knowledge of the cyclization kinetics described by the Jacobson-Stockmayer equations above. By choosing the solvent and ligand to obtain a very fast rate of CuAAC, Lonsdale et al 12 could form PSTY cyclic polymer in less than 9 min at 25 C. This data was further conformed by kinetic simulations.…”
Section: Highlight Wwwpolymerchemistryorg Journal Of Polymer Sciencementioning
confidence: 99%
See 3 more Smart Citations
“…The reason stems for the fact that the faster the reaction the faster the monocyclic will be formed in the reaction mixture, and thus higher feed rates and weight fractions of polymer can be used. 114 Lonsdale et al 12 found that they could significantly increase the weight fraction of starting polymer N 3 -PSTY-B (polystyrene, PSTY) through knowledge of the cyclization kinetics described by the Jacobson-Stockmayer equations above. By choosing the solvent and ligand to obtain a very fast rate of CuAAC, Lonsdale et al 12 could form PSTY cyclic polymer in less than 9 min at 25 C. This data was further conformed by kinetic simulations.…”
Section: Highlight Wwwpolymerchemistryorg Journal Of Polymer Sciencementioning
confidence: 99%
“…114 Lonsdale et al 12 found that they could significantly increase the weight fraction of starting polymer N 3 -PSTY-B (polystyrene, PSTY) through knowledge of the cyclization kinetics described by the Jacobson-Stockmayer equations above. By choosing the solvent and ligand to obtain a very fast rate of CuAAC, Lonsdale et al 12 could form PSTY cyclic polymer in less than 9 min at 25 C. This data was further conformed by kinetic simulations. 114 Cyclic building blocks could further be coupled using ''click'' reactions to create a wide range of cyclic topologies, 64,70 and even used to probe the self-assembly properties of cyclic polymers in water.…”
Section: Highlight Wwwpolymerchemistryorg Journal Of Polymer Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…137 It was also reported that certain water soluble ligands can significantly increase reaction rates. 138 However, for biological applications copper use is detrimental due to the 70 (c), 148 (d), 149 (e), 150 (f), 151 (g), 152 (h), 153 (i), 154 (j), 155 (k), 156 (l), 157 (m), 158 (n), 159 (o), 160 (p), 113 (q), 161 (r), 162 (s), 112 (t), 28 (u), 163 (v), 164 (w), 165 (x), 166 (y), 167 (z). 168 Specific properties of the polymer topologies have been employed in a wide range of applications.…”
mentioning
confidence: 99%